Squalamine: an appropriate strategy against the emergence of multidrug resistant gram-negative bacteria? - Chanaz Salmi; Celine Loncle; Nicolas Vidal; Yves Letourneux; Jacques Fantini; Marc Maresca; Nadira Taïeb; Jean-Marie Pagès; Jean Michel Brunel (PLoS ONE, 2008)
We reported that squalamine is a membrane-active molecule that targets the membrane integrity as demonstrated by the ATP release and dye entry. In this context, its activity may depend on the membrane lipid composition. This molecule shows a preserved activity against bacterial pathogens presenting a noticeable multi-resistance phenotype against antibiotics such as polymyxin B. In this context and because of its structure, action and its relative insensitivity to efflux resistance mechanisms, we have demonstrated that squalamine appears as an alternate way to combat MDR pathogens and by pass the gap regarding the failure of new active antibacterial molecules.